Islamisation or Malaynisation? : a study on the role of Islamic law in the economic development of Malaysia : 1969-1993 - Norhashimah Bt Mohammad, Yasin (1994)
The thesis examines the role of Islam and Shariah (Islamic law) in the economic development of Malaysia and it rejects the assumption that Islam and Shariah inhibit economic development. In contemporary Malaysia, there are two 'policies' adopted by the Government. Firstly, 'Islamisation' which is for the advancement of Islamic law and institution building. Secondly, 'Malaynisation' which promotes the socio-economic development of the Malay ethnic group. The study adopts a holistic approach which covers the political economy of law in Malaysia. The thesis explores the relationship between the two policies considering in particular whether they are essentially the same. The study covers the pre-colonial, colonial and post-colonial periods although the focus is on the post-1969 period which involved the application of the New Economic Policy (NEP). The NEP was a pro-Malay Policy to rectif,' the economic imbalance of the Malays vis-à-vis other communities. Therefore, the focus of this thesis is on the Malay- Muslim population of Peninsular Malaysia who form the bulk of the Bumiputera (indigenous people). Two Bum iputera and Islamic organisations, Bank Islam (BIIMB) and Tabung Haji (TH) as well as the Bumiputera unit trust scheme, Amanah Saham Nasional (ASN) are used as the case studies. Their establishment, structure and organisation are examined. There is a specific focus on the extent to which they are examples of Islamisation or Malaynisation. It is clear that in contemporary Malaysia, Islam and Shariah are being used by the Government to promote economic development. Islamic values have been used to further Malay economic participation in the commercial sector. As a consequence, the economic position of many Malay-Muslims has greatly improved. However, the Government position is questioned by the Islamic opposition who say that the Islamisation policy in many respects is either contrary to Islam or merely cosmetic, and want a 'pure' Islamic approach. The thesis therefore involves a critical examination of the perspectives of both the Government and the Islamic opposition.